Attribution Model of Travel Intention to Internet Celebrity Spots: A Systematic Exploration Based on Psychological Perspective - Yi, Kui; Wang, Qingqing; Xu, Jun; Liu, Bin (Frontiers in Psychology, 2021)
Studies have shown that the empathy process is the main driver of social media influencer' travel intention, but the exact mechanism has not yet been clearly understood by academics. Based on this, this study combines the connotations of meme theory, Theory of Reasoned Action and empathy theory, and applies Amos 26.0 software to empirically analyze 340 valid samples of Web celebrity attractions visitors to explore the effect of attributional elements on social media The study explores the mechanism of attribution on social media'travel intention. (a) The study showed that the mechanism of social media influencer' travel intention can be presented as a psychological model with social media influencer' travel attribution as the independent variable, travel intention as the dependent variable, and the empathy process as the mediating variable; the strength of psychological attribution on affective empathy is higher than external attribution, while the strength of external attribution on cognitive empathy has a relative advantage, and there is a significant difference between them.; empathy process had a significant mediating effect in the relationship between social media influencer' travel attribution and travel intention, and the mediating effect of affective empathy was significantly greater than that of cognitive empathy. This study reveals the segmentation elements with strong explanatory power in social media influencer' travel behavior, examines the practical effect of empathy process in social media influencer' travel intention, and provides theoretical reference for the transformation and upgrading of future tourist places and marketing planning of online communication.